The social advancement of 19th century Greek National Benefactors: The example of Apostolos Arsakis and Constantine Bellios, related to the field of Medicine - Poulakou-Rebelakou, Efi; Mandyla-Koussouni, Maria; Diamandopoulos, Athanasios (DELTOS, 2025)
The study of the history of medicine has expanded considerably to encompass its connections, among others, with literature, the visual arts, poetry, bioethics and sociology. The branch of the latter that analyses medical organisations and institutions and examines how social and cultural factors shape health and medicine, is termed medical sociology.1 However, although as early as 1894 Charles McIntire defined medical sociology as ‘the science of the social phenomena of the physicians themselves as a class apart and separate’2 the collective social advancement of medical practitioners and donors to health institutions has been scarcely investigated. We therefore undertook the present pilot study. Our research, initiated with a painting depicting a group of predominantly nineteenth-century Greek benefactors, aims to present the lives and works of two prominent figures among them: Baron Konstantinos Bellios and Apostolos Arsakis (known in Romania as Apostol Arsache), both closely associated with medicine and medical institutions. In addition to the biographies of these two eminent benefactors, the study explores in depth the social trajectories of these once impoverished, uneducated Vlach boys who rose to become wealthy, educated, aristocratic Greek national benefactors.